Risk stratification of emergency department patients with acute pulmonary thromboembolism: Is chest pain a reason to investigate?. Issue 7 (15th June 2021) - Clements, Warren; McMahon, George AL; Joseph, Tim; Goh, Gerard S; Kuang, Ronny JD; Smit, De Villiers; Varma, Dinesh
Abstract: Background: This study aimed to risk‐stratify chest pain as a presenting symptom in patients with a diagnosis of pulmonary thromboembolism (PE) to assess for any association. In addition, this study aimed to assess traditionally acknowledged PE risk factors in an Australian population. Methods: This was a retrospective single‐centre cohort study assessing patients who presented to our emergency department during the period of 1 January 2019 to 1 January 2020. 730 consecutive patients who went on to computed tomography pulmonary angiography (CTPA) examination after presentation were included. Results: The rate of CTPA being positive in this study was 11.6% (85/730). Chest pain was associated with a non‐significant reduction in the odds of PE (OR 0.774, P  = 0.327). Univariate analysis showed significantly increased odds of a diagnosis of PE with presentation for leg pain/swelling (OR 6.670, P  < 0.001). Multivariate analysis showed increasing age (OR 1.018, 95% CI 1.002–1.034, P  = 0.024), clinical signs of a DVT (OR 3.194, 95% CI 1.803–5.657, P  < 0.001) and positive D‐dimer (OR 1.762, 95% CI 1.011–3.071, P  = 0.046) were associated with increased odds of PE. Conclusion: In this study, Emergency Department presentation with chest pain, whilst the most common reason to perform a CTPA, resulted in reduced odds with regard to the diagnosis of pulmonary thromboembolism. The use of CTPA in this setting may be rationalised according to other factors such as localised leg pain as a symptom, signs of DVT, increasing age or positive D‐dimer.